Wild Grazing Of Beef Cattle In The Buffer Village Of SPTN Region II Sumberwaru Baluran National Park - Siti Azizah; Irfan H. Djunaidi; Achadiah Rachmawati; Rositawati Indrati; Jaisy Aghniarahim Putritamara; Zazin Fahresi Alamanda; Deby Okta Pradana (Green Publisher Indonesia, 2021)
Baluran National Park faces public pressure in the form of illegal grazing, which threatens the preservation of flora and fauna in it. This study aims to analyze illegal grazing activities that threaten the conservation efforts of Baluran National Park in Sumberwaru Village, Asembagus district, Situbondo. Data collection was carried out from April to June 2021 with a qualitative approach. The data were taken from several key informants, namely 3 Baluran National Park officers, the Village Head of Sumberwaru, the Head of Loka Pasuruan, the Situbondo Livestock Service, and 12 extensive semi-intensive beef cattle breeders. The results showed that the behavior of illegal grazing was caused by cultural factors that did not prioritize profit but only as an investment and indicator of social status. As a result, maintenance management is very efficient and depends on feed that can be obtained for free by grazing wildly in the Baluran National Park conservation area. The solution required is a participatory Collaborative Forest Management that benefits all stakeholders.